2019
DOI: 10.1021/acsami.9b14500
|View full text |Cite
|
Sign up to set email alerts
|

A New Aspect for Band Gap Energy of Graphene-Mg2CuSnCoO6-Gallic Acid as a Counter Electrode for Enhancing Dye-Sensitized Solar Cell Performance

Abstract: To develop counter electrodes (CEs) for dye-sensitized solar cells (DSSCs), band gap energy of quaternary semiconductor materials is of great interest. In the present study, a novel graphene sheet based on Mg2CuSnCoO6-Gallic acid nanomaterials (G/MCS@Gallic) was modified with a new Joule heating method, and a laser was applied for measuring band gap energy. Synergistic effect between graphene and Mg2CuSnCoO6-Gallic ensured excellent electron transport through the electrode and low band gap energy. The large su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The determination of the acidic surface functional groups was performed using the Boehm titration method, 59 with modifications. 60,61 For this, 0.05 g of the CRH sample was added to three Erlenmeyer flasks, each containing NaOH, Na 2 CO 3 , and NaHCO 3 (0.1 mol L À1 ; 10 mL). The solutions were stirred for 24 h at room temperature.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…The determination of the acidic surface functional groups was performed using the Boehm titration method, 59 with modifications. 60,61 For this, 0.05 g of the CRH sample was added to three Erlenmeyer flasks, each containing NaOH, Na 2 CO 3 , and NaHCO 3 (0.1 mol L À1 ; 10 mL). The solutions were stirred for 24 h at room temperature.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…It was also reported that a counter electrode composed of carbon black, and a conductive polymer with conductive glass, can have a conversion efficiency reaching 7.24% [ 32 ]. Moreover, due to its high chemical stability, electrical conductivity, thermal conductivity, and excellent mechanical properties [ 33 ], multi-walled carbon nanotubes (MWCNTs) have recently been reported on multiple accounts to show good electronic properties in the production of DSSCs [ 34 , 35 , 36 ]. Samantaray et al prepared the counter electrode of DSSCs using carbon nanotubes, reporting a conversion efficiency of 7.00–7.81% [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers pay more attention to the development of low cost and high activity nano carbon materials, conductive polymers and their composite materials, etc. [ 16 , 17 , 18 ]. It is worth noting that in recent years, flexible DSSCs assembled on non-planar fibrous conductive substrates with high curvature and excellent stitchability have been constantly developed, which break through the limitations of traditional flat substrates and have the advantages of bendability, light weight and wide application prospects [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%